Prospect of Genetics Improvement of Physic Nut (Jatropha curcas L.) - . HASNAM (Puslitbang Perkebunan, 2011)
The development of physic nut in Indonesia is hampered by technological obstacles, limited infrastructure, and institutional constraints. Limited radiation, due to shading, exeside or lock of rainfall, nutrient deficiencies, and various changes in environmental condition results in variation in male to female flower ratio and alteration of reproductive system that lowers plant productivity. The crop productivity is too low and costly to manage physic nut plantation commercially. The potential of Jatropha curcas L. has not yet been realized. One of the reasons is the lack of high yielding varieties with high oil content. As an often cross pollinated crop, the following methods can be employed to exploit its genetic variation such as : (a) mass selection, (b) utilization of hybrid and inter-specific hybridization, (c) recurrent selection, and (d) molecular breeding. Assessment of superior genotypes, exploitation of heterosis effect, utilization of inter-specific hybridization, and application of genetic transformation through agro-bacterium vector mediated or particle shooting will bring in the increase in yield and oil traits.Keywords: Jatropha curcas L., environment, selection, yield, plus tree, molecular, genetic transformation, agro-bacterium vector, particle shooting.